2022
DOI: 10.1007/s11357-022-00623-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in circulating IGF-1 associates with impaired neurovascular coupling responses in older adults

Abstract: Impairment of moment-to-moment adjustment of cerebral blood flow (CBF) to the increased oxygen and energy requirements of active brain regions via neurovascular coupling (NVC) contributes to the genesis of age-related cognitive impairment. Aging is associated with marked deficiency in the vasoprotective hormone insulin-like growth factor-1 (IGF-1). Preclinical studies on animal models of aging suggest that circulating IGF-1 deficiency is causally linked to impairment of NVC responses. The present study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…Age-related GH/IGF-1 deficiency has been causally linked to the genesis of aging phenotypes in various organ systems, including the cardiovascular system, musculoskeletal system and the central nervous system ( 95 105 ). Patients with decreased GH/IGF-1 have an increased risk of VCID and other forms cardiovascular and cerebrovascular disease ( 94 , 106 108 ), including gait and cognitive impairment ( 109 111 ), as well as diabetes mellitus ( 106 ). Older adults with low circulating IGF-1 levels have 39% higher risk of cardiovascular mortality ( 112 ).…”
Section: Regulation Of Aging Processes By the Gh/igf-1 Axismentioning
confidence: 99%
See 3 more Smart Citations
“…Age-related GH/IGF-1 deficiency has been causally linked to the genesis of aging phenotypes in various organ systems, including the cardiovascular system, musculoskeletal system and the central nervous system ( 95 105 ). Patients with decreased GH/IGF-1 have an increased risk of VCID and other forms cardiovascular and cerebrovascular disease ( 94 , 106 108 ), including gait and cognitive impairment ( 109 111 ), as well as diabetes mellitus ( 106 ). Older adults with low circulating IGF-1 levels have 39% higher risk of cardiovascular mortality ( 112 ).…”
Section: Regulation Of Aging Processes By the Gh/igf-1 Axismentioning
confidence: 99%
“…IGF-1 may also play a role in regulating baseline CBF. Magnetic resonance imaging studies have shown that baseline mean blood flow velocity in the middle cerebral artery is decreased in aged vs. young cohorts, and that flow is significantly correlated with serum IGF-1 levels ( 94 ). Overall, IGF-1 has a central role in regulation of CBF by contributing to pressure- and flow-dependent responses of cerebral arteries, plays a role in structural adaptation to hypertension, and contributes to adaptive ECM changes and in ECM-related gene expression.…”
Section: Role Of Gh/igf-1 In Regulation Of Cerebrovascular Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aging is a major risk factor for vascular cognitive impairment (VCI), the second most common form of cognitive impairment after AD. A wide array of functional and structural alterations of the cerebral microvasculature were shown to contribute to the pathogenesis of VCI ( 74 77 ) including cerebromicrovascular rarefaction ( 5 , 78 ) and a related decline in cerebral blood flow ( 79 , 80 ), microhemorrhages ( 81 84 ), microinfarcts ( 85 , 86 ), impaired glymphatics function ( 87 ), blood brain barrier disruption ( 88 , 89 ), consequential neuroinflammation ( 90 ), impaired neurovascular coupling ( 91 93 ) systemic endothelial dysfunction ( 4 , 94 ) and endothelial senescence ( 95 ). Stroke is an important consequence of cerebrovascular aging.…”
Section: Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 99%